Reconfigurable UWB pulse generator based on pulse shaping in a nonlinear optical loop mirror and differential detection - Huang, Tianye (2013)
A reconfigurable impulse radio ultra-wideband (UWB) pulse generator for various UWB shapes (e.g., monocycle, doublet, and triplet pulses) based on a nonlinear optical loop mirror (NOLM) and differential detection is proposed and experimentally demonstrated. The proposed approach can be used with different modulation formats and may be suitable for implementation in future low-cost, high-speed, short-range UWB wireless access applications.